Novel Channel Hopping Sequence Approaches to Rendezvous for Vanets - Soto-Gomez, J (Institute of Electrical and Electronics Engineers Inc., 2017)
ehicular ad hoc networks (VANETs) have emerged as a paradigm for sharing information among vehicles and infrastructure that has the potential to provide road safety and travellers comfort. The bandwidth limitation is one of the main challenges of this technology, however, the growing perspectives of applications demand more and more service channels. In this work we propose two novel channel hopping (CH) sequence approaches to rendezvous, in order to allow VANET applications to use unlicensed channels. Besides, practical implementation considerations to reduce the search space and to replace the busy channels are discussed. We evaluate the performance of the proposed strategies in the presence of users competing for the available channels. Our results indicate that with a suitable CH sequence it is possible to increase the number of useful channels for rendezvous and thus decrease the percentage of failed rendezvous. © 2017 IEEE.